2020
DOI: 10.1111/sji.12988
|View full text |Cite
|
Sign up to set email alerts
|

TLR10: Insights, controversies and potential utility as a therapeutic target

Abstract: The Toll-like receptor (TLR) family acts as a bridge connecting innate and acquired immunity. TLR10 remains one of the least understood members of this family. Some studies have examined TLR10 ligands, dimerization of TLR10 with other TLRs, and downstream signalling pathways and functions, but they have often arrived at conflicting conclusions. TLR10 can induce the production of proinflammatory cytokines

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 96 publications
(283 reference statements)
0
30
0
Order By: Relevance
“…By contrast, TLR3, TLR7, TLR8, and TLR9 localize to endosomes, where they detect nucleic acids derived from viruses, bacteria, or damaged cells. The roles of TLR10 and TLR11 remain unclear, and TLR10 seems to be able to form dimers with TLR1-2, TLR4, TLR6, and TLR8 [ 84 , 85 , 86 , 87 ]. Once the PRRs on the surface of the target cell have been activated by PAMPs or DAMPs, they initiate the innate immune response by producing chemokines, cytokines, and antimicrobial peptides (AMPs).…”
Section: C Acnes and Inflammationmentioning
confidence: 99%
“…By contrast, TLR3, TLR7, TLR8, and TLR9 localize to endosomes, where they detect nucleic acids derived from viruses, bacteria, or damaged cells. The roles of TLR10 and TLR11 remain unclear, and TLR10 seems to be able to form dimers with TLR1-2, TLR4, TLR6, and TLR8 [ 84 , 85 , 86 , 87 ]. Once the PRRs on the surface of the target cell have been activated by PAMPs or DAMPs, they initiate the innate immune response by producing chemokines, cytokines, and antimicrobial peptides (AMPs).…”
Section: C Acnes and Inflammationmentioning
confidence: 99%
“…Furthermore, TLR10 may heterodimerize with TLR2 to recognize LPS and heat shock proteins (HSP60) of Helicobacter pylori ( H. pylori ) to trigger innate immune responses. PamCysPamSK4, a diacylated peptide, could be recognized by the TLR10 homodimer and TLR1/TLR10 heterodimer (Fore et al 2020 ; Su et al 2020 ). A recent study has shown that TLR10 can enhance gp41-mediated IL-8 induction and NF-κBα activation and modulate HIV-1 infection and integration independent of TLR2 (Henrick et al 2019 ).…”
Section: Lipoprotein Is the Predominant Ligand For The Tlr2 Subfamilymentioning
confidence: 99%
“…Moreover, TLR10 can upregulate chemokine ligand 20 and IL-8 expression in response to Listeria monocytogenes (EGD) and Salmonella typhimurium ( S. typhimurium ) infections, while the infection with H1N1 (A/HK/54/98) and H5N1 (A/Vietnam/3212/04) influenza virus leads to an increased TLR10 expression and triggers the induction of pro-inflammatory cytokines and interferons in the host (Latorre et al 2016 ; Lee et al 2014a , 2014b ; Regan et al 2013 ). TLR10 is the only TLR that can antagonize TLR2 activity, inhibit downstream signal transductions, and suppress B cell adaptive immune responses (Hess et al 2017 ; Oosting et al 2014 ; Su et al 2020 ). It acts as a negative regulator of both MyD88 and TRIF-mediated signaling, suppressing the degradation of IκB and the phosphorylation of MAPKs through the production of IFN-β (Jiang et al 2016 ).…”
Section: Lipoprotein Is the Predominant Ligand For The Tlr2 Subfamilymentioning
confidence: 99%
“…Furthermore, depending on the type of dimer formed, TLR10 is suggested to be able to produce a pro-inflammatory or an inhibitory effect. 100 Similarly, mixed results have emerged for the role of TLR10 in RA. In line with TLR10 having an anti-inflammatory role, TLR10 mRNA is expressed at lower levels in PBMCs of RA patients with active disease, whilst a missense mutation (I473T) has been associated with increased disease severity and a lower response to the anti-TNF biological infliximab.…”
Section: Tlr10mentioning
confidence: 99%